Developing a Digital Bilingual Storybook for Teaching English with The Insertion of Spirituality Value in Fifth Grade Students - I Made Dharma Prananta; Luh Putu Artini; Kadek Sintya Dewi (Edu-Ling: Journal of English Education and Linguistics, 2026)
This study aimed to develop a digital bilingual storybook integrating spirituality values for Grade 5 elementary school students and evaluate its quality as an instructional medium for English language learning. This study employed a Design and Development (D&D) model adapted from Huhta et al. (2013), consisting of two stages: design and development. The design stage involved conducting a needs analysis through document analysis and interviews, whereas the development stage included designing the storyline, writing the story script, developing the prototype, and conducting expert validation. The digital bilingual storybook developed in this study is titled Jojo and His Amazing Body. Spirituality values were integrated through the storyline, dialogues, illustrations, and pre-reading, while-reading, and post-reading activities. The product was evaluated by two experts in English pedagogy. The quantitative evaluation results showed that the two experts assigned scores of 149 and 148 out of 150, respectively, and both scores fell into the “Excellent” category. Furthermore, the qualitative feedback indicated that the developed storybook was relevant, engaging, visually appealing, linguistically appropriate for the students’ characteristics, and supportive of English language learning and the reinforcement of spirituality values. Therefore, the developed digital bilingual storybook was considered highly appropriate as an instructional medium for Grade 5 elementary school students while simultaneously promoting spirituality values.